QUALITY ASSURANCE INTERNATIONALIZATION IN THE EUROPEAN HIGHER EDUCATION AREA: LEGISLATIVE FOUNDATIONS - Inna Yeremenko (Pavlo Tychyna Uman State Pedagogical University, 2018)
The article clarifies the genesis of forming a European dimension of quality assurance in higher education. It provides for the analysis of official documents of the EU and the Bologna Process, which lay the basis for quality assurance in higher education within the European Higher Education Area. Particular emphasis is put on the progressand first outcomes of the development of the quality assurance in higher education at the national and supranational levels. A special focus is placed ona series of joint actions taken by European countries to improve the quality of higher education through developing the quality assurance mechanisms to gain more transparency, accountability and legitimacy in European higher education systems. These actions include the launch ofthe Institutional Evaluation Program (IEP),the European pilot projects for evaluating quality in higher education,the creation of the European Network for Quality Assurance (ENQA) renamed into the European Association for Quality Assurance in Higher Education (ENQA), the creation of the Joint Quality Initiative (JQI) and the European Quality Assurance Register (EQAR). The adoption of the Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG) is analyzed as an efficient way of creating the legal and regulatory environment in the European Higher Education Area.